The Prevalence and Pathophysiology of Chemical Sense Disorder Caused by the Novel Coronavirus - Narayanan, Sareesh Naduvil; Shivappa, Pooja; Padiyath, Sreeshma; Bhaskar, Anand; Li, Yan Wa; Merghani, Tarig Hakim (Frontiers in Public Health, 2022)
Emerging viral infections are a ceaseless challenge and remain a global public health concern. The world has not yet come back to normal from the devastating effects of the highly contagious and pathogenic novel coronavirus, or Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Olfactory and taste dysfunction are common in patients infected by the novel coronavirus (COVID-19). In light of the emergence of different coronavirus variants, it is important to update the prevalence and pathophysiology of these side effects. In this review, articles published on the prevalence of olfactory and taste dysfunction from COVID-19 and their possible pathophysiologic mechanisms have been reviewed and reported. The modulatory role of different SARS-CoV-2 variants on the chemical senses is then described. The clinical relevance of chemical sense disorder and its long-term morbidity and management is also discussed.